The Role of Gut Microbiota in Tumor Immunotherapy - Miao Wu; Jiawei Bai; Chengtai Ma; Jie Wei; Xianjin Du (Journal of Immunology Research)
Tumor immunotherapy is the fourth therapy after surgery, chemotherapy, and radiotherapy. It has made great breakthroughs in the treatment of some epithelial tumors and hematological tumors. However, its adverse reactions are common or even more serious, and the response rate in some solid tumors is not satisfactory. With the maturity of genomics and metabolomics technologies, the effect of intestinal microbiota in tumor development and treatment has gradually been recognized. The microbiota may affect tumor immunity by regulating the host immune system and tumor microenvironment. Some bacteria help fight tumors by activating immunity, while some bacteria mediate immunosuppression to help cancer cells escape from the immune system. More and more studies have revealed that the effects and complications of tumor immunotherapy are related to the composition of the gut microbiota. The composition of the intestinal microbiota that is sensitive to treatment or prone to adverse reactions has certain characteristics. These characteristics may be used as biomarkers to predict the prognosis of immunotherapy and may also be developed as “immune potentiators” to assist immunotherapy. Some clinical and preclinical studies have proved that microbial intervention, including microbial transplantation, can improve the sensitivity of immunotherapy or reduce adverse reactions to a certain extent. With the development of gene editing technology and nanotechnology, the design and development of engineered bacteria that contribute to immunotherapy has become a new research hotspot. Based on the relationship between the intestinal microbiota and immunotherapy, the correct mining of microbial information and the development of reasonable and feasible microbial intervention methods are expected to optimize tumor immunotherapy to a large extent and bring new breakthroughs in tumor treatment.